Improving accuracy and efficiency of CFD predictions of propeller open water performance (Journal of Naval Architecture and Marine Engineering, 2019)
This research proposes mesh and domain optimization strategies for a popular Computational Fluid Dynamics (CFD) technique to estimate the open water propulsive characteristics of fixed pitch propellers accurately and time-efficiently based on examining the effect of various mesh and computation domain parameters. It used a Reynolds-Averaged Navier-Stokes (RANS) solver to predict the propulsive performance of a fixed pitch propeller with varied meshing, simulation domain and setup parameters. The optimized mesh and domain size parameters were selected using Design of Experiments (DoE) methods enabling simulations in a limited memory and in a timely manner without compromising the accuracy of results. The predicted thrust and torque for the propeller were compared to the corresponding measurements for determining the prediction accuracy. The authors found that the optimized meshing and setup arrangements reduced the propeller opens simulation time by at least a factor of six as compared to the generally popular CFD parameter setup. In addition, the accuracy of propulsive characteristics was improved by up to 50% as compared to published simulation results. The methodologies presented in this paper can be similarly applied to other simulations such as calm water ship resistance, ship propulsion etc. to systematically derive the optimized meshing arrangement for simulations with minimal simulation time and maximum accuracy. This investigation was carried out using a commercial CFD package; however, the findings can be applied to any RANS solver.